Raising Preschool Children in the Family (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article discusses specific psychological aspects of the formation of behavioral characteristics in the upbringing of children in the family, the views of psychologists on the behavioral education of a child, the essence of aspects of parenting and child behavior.